Marca d'água Digital Robusta via Decomposiçâo de Imagens - Lopes, I. O. [UNESP]; Da Silva, A. C.R. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
Digital watermarking is a technique that can be utilized for authenticity verification or for the copyright protection of digital data. The finality to which the technique will be utilized is that determines if the method of watermarking must be fragile or robust. The robust watermarking schemes are usually utilized for the copyright protection, so, these schemes must be resistant to attacks. To obtain more robustness, the techniques of watermarking embed the watermark in the points more significant of the data. In this work is presented a technique of watermarking applied to digital images. The technique consists in decomposing a image in part structural and in part of details (textures, edges, noises) that are the components more significant of a image. After the decomposition is done, the watermark is embedded in the part of details, which is added the structural part and then obtained the watermarked image. The process to watermarking image is based in techniques to spread spectrum and utilizes the transformed discrete cosine. Tests were done and demonstrate that the technique proposes proportions good results.
Robust digital watermarking by image decomposition
Keywords: Authenticity verification; Copyright protection; Image Decomposition; Robustness; Watermarking